2018
DOI: 10.1371/journal.pone.0202415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat and pectinase maceration on phenolic compounds and physicochemical quality of Strychnos cocculoides juice

Abstract: Strychnos cocculoides fruit is an important food source for rural populations in Zimbabwe in times of scarcity. Its thick pulp tightly adheres to its seeds, causing pulp extraction constraints and waste during processing, leading to underutilisation. Therefore, pectinase maceration combined with heat treatments was studied to improve juice yield and juice quality. Metabolite profiling according to the heat map, FancyTile chromatic scale approach and phenolic compound content were used to compare the identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
2
7
0
1
Order By: Relevance
“…Cluster P2 included all the dicaffeoylquinic acid isomers (3,5-DiCQA,1,5-DiCQA, 3,4-DiCQA and 4,5-DiCQA) which were major phenolics in H. tuberosus leaves, while cluster P1 contained caffeoylquinic acid isomers (3-CQA,4-CQA and 5-CQA) and other minor phenolic compounds. HCA results showed that determinants such as genotype, different extraction methods, the growth location and harvesting time might affect the metabolites, which was in accordance with previous studies [17].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Cluster P2 included all the dicaffeoylquinic acid isomers (3,5-DiCQA,1,5-DiCQA, 3,4-DiCQA and 4,5-DiCQA) which were major phenolics in H. tuberosus leaves, while cluster P1 contained caffeoylquinic acid isomers (3-CQA,4-CQA and 5-CQA) and other minor phenolic compounds. HCA results showed that determinants such as genotype, different extraction methods, the growth location and harvesting time might affect the metabolites, which was in accordance with previous studies [17].…”
Section: Resultssupporting
confidence: 91%
“…The relationships between samples and bioactive compounds are represented by the distances. The closer the distance of samples is, the more similar the samples are [17]. As displayed in Figure 3, the two classes of 13 kinds of phenolics and the two main clusters of extracts samples were obviously classified by HCA.…”
Section: Resultsmentioning
confidence: 99%
“…This was expected as in previous studies we found that chlorogenic acid (an ester of caffeic acid and quinic acid) accounts for 65 % of the phenolic compounds identified in monkey orange juice (Ngadze et al,. 2018).…”
Section: In-vitro Bioaccessibility Of Phenolic Compoundssupporting
confidence: 86%
“…Porridge preparation is presented in figure 5.1. Juice preparation was as described by Ngadze et al,2018. The final product was a homogenous slurry, free from lumps.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation